Factors Influencing Students' Interest in Taking the Accounting Technician Certification Exam - Fariyana Kusumawati; Yudhanta Sambharakreshna; Anis Wulandari (Eduvest - Journal of Universal Studies, 2026)
This study aims to examine student interest in taking the accounting bachelor's certification exam in the accounting study program at Trunojoyo University, Madura. Factors in this study include facilities and infrastructure, instructor competence, learning methods, competency certification implementation, and certification benefits. This study used a multiple linear regression model. The population and sample were active accounting students in their fourth semester and above. The sampling technique used was purposive sampling. The results showed that facilities and infrastructure, learning models, and certification benefits influenced student interest in taking the accounting professional certification exam. Instructor competence and competency certification implementation did not. The impact of this study on students is that it can increase motivation to obtain competency certification, and for the accounting study program, it can improve the quality of learning supported by adequate facilities and infrastructure